(untitled) (Philological Studies, 2019)
The article is related to the problem of assimilation of internationalism and the influence on the process of the native language. Considered lexical interference in the assimilation of internationalism that has one meaning in their native language and some in the foreign language. The material for the study is based on data of the association experiment.